(-)-Epigallocatechin-3-Gallate Inhibits eNOS Uncoupling and Alleviates High Glucose-Induced Dysfunction and Apoptosis of Human Umbilical Vein Endothelial Cells by PI3K/AKT/eNOS Pathway - Zhang Z (Dove Medical Press, 2020)
Zhiyong Zhang,1 Daimin Zhang2 1Department of Cardiology, Suqian First People’s Hospital, Suqian, Jiangsu 223800, People’s Republic of China; 2Department of Cardiology, Nanjing First Hospital, Nanjing Medical University, Nanjing, Jiangsu 210006, People’s Republic of ChinaCorrespondence: Daimin ZhangDepartment of Cardiology, Nanjing First Hospital, Nanjing Medical University, 68 Changle Road, Nanjing, Jiangsu 210006, People’s Republic of ChinaTel +86 13915987283Fax +86 25-52271341Email dmzhangzdm@163.comIntroduction: Diabetes can increase the risk of cardiovascular disease. This study aimed to explore the effect of (-)-epigallocatechin-3-gallate (EGCG) on high glucose (HG)-induced dysfunction and apoptosis of vascular endothelial cells.Materials and Methods: The viability of human umbilical vein endothelial cells (HUVECs) treated with different concentrations and times of EGCG was detected by CCK-8 assay. The expression levels of ROS, NO and BH4 in HUVECs after treatment were detected by respective ELISA kits. The expression of p-eNOS, eNOS, NOX4, bcl2, bax, cleaved-caspase3, caspase3, p-PI3K, p-AKT, PI3K and AKT in HUVECs was detected by Western blot analysis. The apoptosis of HUVECs after treatment was analyzed by TUNEL assay.Results: The viability of HUVECs was not obviously changed when treated with different concentrations and times of EGCG. The expression of ROS, NOX4 and eNOS (monomer) was increased, while the expression of NO, p-eNOS, eNOS, BH4 and eNOS (dimer) was decreased in HUVECs of HG group. EGCG could gradually reverse the effect of high glucose on HG-treated HUVECs from 10 μM to 50 μM. The apoptosis of HUVECs was also increased in HG group and EGCG decreased the apoptosis of HUVECs. PI3K/AKT signaling pathway was suppressed in HG-treated HUVECs while activated by EGCG treatment. When the PI3K/AKT signaling pathway was inhibited by LY294002 (AKT inhibitor), the protective effect of EGCG on HG-treated HUVECs was weakened.Conclusion: EGCG could inhibit eNOS uncoupling and alleviate endothelial dysfunction and apoptosis of HG-treated HUVECs by activating the PI3K/AKT/eNOS pathway.Keywords: (-)-epigallocatechin-3-gallate, eNOS uncoupling, endothelial dysfunction, apoptosis, human umbilical vein endothelial cells